Ficus septica Burm. f.: A comprehensive review of its ethnomedicinal uses, phytochemistry, and pharmacological properties - Tazkiyatan Isria; Berna Elya; Roshamur Cahyan Forestrania; Muhammad Hanafi (Faculty of Pharmacy, Universitas Pancasila, 2026)
Ficus septica Burm. f. is a significant medicinal plant within the Moraceae family, recognized for its extensive ethnomedicinal application throughout Southeast Asia, including Indonesia, the Philippines, and Papua New Guinea. It has been used to treat various conditions, from dermatological infections and fever to digestive disturbances. This review aimed to compile and critically evaluate the existing scientific literature on the botany, ethnomedicine, phytochemistry, and pharmacological potential of F. septica. A systematic literature search and selection process was conducted following the PRISMA guidelines to ensure transparency and reproducibility, supported by a narrative synthesis approach. Phytochemical investigations have consistently demonstrated that this species is abundant in diverse secondary metabolites, notably phenanthroindolizidine alkaloids (such as antofine, tylophorine, and ficuseptine), which serve as primary chemical markers. In conjunction with other flavonoids, terpenoids, and phenolic compounds, these compounds are responsible for many scientifically validated bioactivities. Pharmacological evidence highlights its anticancer capabilities, including apoptosis induction, cell cycle arrest, and anti-metastatic activity. Furthermore, it exhibits broad-spectrum antimicrobial activity, including antibacterial, antifungal, antiviral, and antiprotozoal effects. Its antioxidant, anti-inflammatory, and wound-healing properties have been extensively documented. This review affirms that contemporary scientific findings substantiate the traditional utilization of F. septica and underscores its potential as a valuable source for developing novel therapeutic agents, particularly in oncology and infectious disease management.